Preterm birth update in Australasia: A report of the international symposium of Preterm Birth International Collaborative-Australasia branch - Qiao, Chong; Menon, Ramkumar; Ahn, Ki Hoon; Suzuki, Shunji; Kshetrapal, Pallavi; Georgiou, Harry Michael; Mesiano, Sam; Zhong, Nanbert (Frontiers in Pediatrics, 2022)
Preterm birth (PTB) is one of the most important problems that pose dilemmas for both the obstetrician and neonatologist, placing a heavy burden psychologically and financially on the families involved, and triggering high socio-economic costs to the public healthcare. The rate of PTB in Asian countries has been ranked at top globally. To reduce the PTB rate, to promote the prevention and intervention for PTB, and to better understand the pathophysiology underlying PTB, the Preterm Birth International Collaborative Australia branch (PREBIC-AA) was launched in 2017. A series scientific activities including organizing annual research symposiums has been planned and organized among Australasian countries. Here we briefly updated the current progress in clinical management and translational research on PTB in Australasian countries that have been participated in PREBIC-AA.